Mapping Pharmacological Network of Multi-Targeting Litchi Ingredients in Cancer Therapeutics - Cao, Sisi; Han, Yaoyao; Li, Qiaofeng; Chen, Yanjiang; Zhu, Dan; Su, Zhiheng; Guo, Hongwei (Frontiers in Pharmacology, 2020)
Considerable pharmacological studies have demonstrated that the extracts and ingredients from different parts (seeds, peels, pulps and flowers) of Litchi exhibited anticancer effects by affecting the proliferation, apoptosis, autophagy, metastasis, chemotherapy and radiotherapy sensitivity, stemness, metabolism, angiogenesis and immunity via multiple targeting. However, there is no systematical analysis on the interaction network of "multiple ingredients-multiple targets-multiple pathways" anticancer effects of Litchi. In this study, we summarized the confirmed anticancer ingredients and molecular targets of Litchi based on published articles and applied network pharmacology approach to explore the complex mechanisms underlying these effects from a perspective of system biology. The top ingredients, top targets and top pathways of each anticancer function were identified using network pharmacology approach. Further intersecting analyses showed that Epigallocatechin gallate (EGCG), Gallic acid, Kaempferol, Luteolin and Betulinic acid were the top ingredients which might be the key ingredients exerting anticancer function of Litchi, while BAX, BCL2, CASP3, and AKT1 were the top targets which might be the main targets underling the anticancer mechanisms of these top ingredients. These results provided references for further understanding and exploration of Litchi as therapeutics in cancer as well as the application of "Component Formula" based on Litchi's effective ingredients.